QUANTIFICAÇÃO DE MACROELEMENTOS E MICROELEMENTOS PRESENTES EM DIFERENTES MARCAS DE CIGARROS BRASILEIROS E PARAGUAIOS - Teófilo Gonçalves Rafael da Silva (2024)
Cigarettes contain several chemical compounds in their composition. However, there are few studies and continuous monitoring involving the quantification of toxic metals present in tobacco, filters and smoke from Brazilian cigarettes. Therefore, the objective of this study was to quantify aluminum, arsenic, barium, cadmium, chromium, chromium, copper, iron, mercury, manganese, nickel and lead in samples of cigarettes sold and produced in Brazil and Paraguay. A total of 24 cigarette samples from three Brazilian and three Paraguayan brands were acquired through direct purchase. Tobacco and filter samples were digested using nitric acid and hydrogen peroxide in the presence of a digester. After acid digestion, the quantification of chemical elements in tobacco and filters from Brazilian and Paraguayan cigarettes was carried out using inductively coupled plasma optical emission spectrometry (ICP OES). The following concentrations of elements were quantified in Fox, Chesterfield, Mill, Marlboro, Dunhill and Hudson cigarette brands: Al (10.750 ± 0.368 - 59.4155 ± 0.8239 mg/kg), As (2.0280 ± 0.065 - 10 .8617 ± 0.12 mg/kg), Ba (11.3706 ± 0.0564 - 19.9368 ± 0.3549 mg/kg), Cd (0.0501 ± 0.0223 - 0.2806 ± 0.0257 mg/kg), Cr (0.4751 ± 0.0556 - 0.6224 - 0.0526 mg/kg), Cu (5.7339 ± 0.14118 - 8.4264 ± 0.4039 mg/kg), Fe (243.2909 ± 4.6954 - 304.0686 ± 12.5182 mg/kg), Mn (141.4208 ± 5.8344 - 327.1850 ± 8.8962 mg/kg), Ni (0.1535 ± 0 .0416 to 0.6274 ± 0.0309 mg/kg), Pb, (0.5852 ± 0.1300 to 0.7656 ± 0.1534 mg/kg) and Zn (13.2660 ± 0.0300 to 25, 8462 ± 0.1748 mg/kg). The element Hg is below the limit of detection (LOD) in all tobacco samples. The elements Mn, Zn, Ba, Cu, Pb, Cr, Cd, and Ni in the filters were below the LOD. The average concentration values of Al, Mn, As and Pb are higher than those obtained in other countries. The average values of concentrations of Ba, Cd, Cu, Ni in the tobacco studied in this research are lower than those obtained in countries such as Ghana and the USA. The average concentrations of Zn are lower than the concentration values obtained in tobacco in research carried out in Iran and Brazil. There is the presence of elements such as Al, As, Cu and Fe in cigarette filters, which can contaminate the environment and be harmful to human health. Future research must be carried out in Brazil to investigate the level of contamination from discarded cigarette butts and filters, as well as risk calculations due to ingestion, inhalation and dermal contact must be carried out. New research must be carried out to quantify and adulterate cigarettes. Keywords: Heavy metals, ICP OES, Cigarettes, Toxicity.